EFFECT OF NEGATIVE INTEREST RATE POLICY (NIRP) ON BANK PROFITABILITY: CROSS-COUNTRY ECONOMETRIC STUDY - Kopbayev, Alim (Nazarbayev University School of Sciences and Humanities, 2021)
The Negative Interest Rate Policy (NIRP) introduction was dictated with an expansionary motive of the central banks. Unconventional monetary policy is still not fully analyzed, and there are no signs that in the future policy rates might become positive. This essay investigates the impact of NIRP on bank profitability, Return on Assets (ROA). The difference-in-difference estimation method showed a small and insignificant decrease of ROA of banks in those countries where NIRP was conducted. Two effects contribute to this result. First, net interest-related income dropped for the treatment group banks. Secondly, banks offset a reduction of interest-related profits by an increase in non-interest income, which includes commissions and fees.
Keywords: bank; Negative Interest Rate Policy; Type of access: Open Access